Exploring healthcare providers’ perspectives of the paediatric discharge process in Uganda: a qualitative exploratory study - Nemetchek, Brooklyn; Khowaja, Asif; Kavuma, Anthony; Kabajaasi, Olive; Owilli, Alex Olirus; Ansermino, J Mark; Fowler-Kerry, Susan; Jacob, Shevin T; Kenya-Mugisha, Nathan; Kabakyenga, Jerome; Wiens, Matthew O (BMJ open, 2019)
Introduction The burden of childhood mortality continues to be born largely by low-income and middle-income countries. The critical post discharge period has been largely neglected despite evidence that mortality rates during this period can exceed inpatient mortality rates. However, there is a paucity of data on the paediatric discharge process from the perspective of the healthcare provider. Provider perspectives may be important in the development of an improved understanding of the barriers and facilitators to improving the transition from hospital to home. Objectives: To explore healthcare providers’ and facility administrators’ perspectives of the paediatric discharge process with respect to: (1) current procedures, (2) barriers and challenges, (3) ideas for change, (4) facilitators for change and (5) the importance of discharge planning. Design A qualitative exploratory approach using focus groups (14) and in-depth interviews (7). Setting This study was conducted at seven hospitals providing paediatric care in Uganda. Results Current discharge procedures are largely based on hospital-specific protocols or clinician opinion, as opposed to national guidelines. Some key barriers to an improved discharge process included caregiver resources and education, critical communication gaps, traditional practices, and a lack of human and physical resources. Teamwork and motivation to see improved paediatric transitions to home were identified as facilitators to implementing the ideas for change proposed by participants. The need for a standardised national policy guiding paediatric discharges, implemented through education at many levels and coupled with appropriate community referral and follow-up, was broadly perceived as essential to improving outcomes for children. Conclusions Although significant challenges and gaps were identified within the current health system, participants’ ideas and the identified facilitators provide a significant basis from which change may occur. This work can facilitate the development of sustainable and effective interventions to improve post discharge outcomes in Uganda and other similar settings.